Impact of Gaming Disorder Against Adolescent Emotional Intelligence: A Systematic Review - Ari Dwi Sulaksono; Wisnu Barlianto; Heni Dwi Windarwati (International Journal of Science and Society, 2020)
Emotional intelligence consists of self-awareness, self-regulation, self-motivation, self-empathy and social skills. Gaming disorder in adolescents can lead to self-concept disorder, depression, social dysfunction and even mental disorders. The systematic aim of this review is to identify the phenomenology of the impact of gaming disorder on adolescent emotional intelligence. The stages in making this systematic review create questions, identification, eligibility, article inclusion selection, screening, and appraisal in an international database that is Science Direct, ProQuest and PubMed. Selection was done with PRISMA flow-diagrams and criticized with the JBI tool. After obtaining 23 relevant articles, they are then analyzed into a systematic review. Gaming disorder is a problem of great concern in various countries. Gaming disorder is the main trigger affecting the emotional intelligence of adolescents today. The highest aspect resulting from gaming disorder is in the aspect of self-regulation, then aspects of self-awareness, self-empathy, self-motivation and social skills also experience a significant impact. This disorder, if it continues with higher intensity, can cause sufferers to experience negative things in their lives. Emotional intelligence is very important to be mastered in life, if emotional intelligence has been disturbed due to gaming disorder then the five aspects of emotional intelligence will also be disturbed. The fact that gaming disorder is empirically proven can have an impact on adolescent emotional intelligence. Thus, conducting additional research in Indonesia and also the world is very important to understand gaming disorder and how to handle it.